Spells for forgetting - Young, Adrienne, 1985- (Delacorte Press, 2022)
"Emery Blackwood's life was forever changed on the eve of her high school graduation, when the love of her life, August Salt, was accused of murdering her best friend, Lily. Now, she is doing what her teenage self swore she never would: living a quiet existence among the community that fractured her world in two. She'd once longed to run away with August, eager to escape the misty, remote shores of Saiorse Island and chase new dreams; now, she maintains her late mother's tea shop and cares for her ailing father. But just as the island, rooted in folklore and tradition, begins to show signs of strange happenings, August returns for the first time in fourteen years and unearths the past that no one wants to remember. August Salt knows he is not welcome on Saiorse, not after the night that changed everything. As a fire raged on at the Salt family orchard, Lily Morgan was found dead in the dark woods, shaking the bedrock of their tight-knit community and branding August a murderer. When he returns to bury his mother's ashes, he must confront the people who turned their backs on him and face the one wound from the past that has never healed-Emery. But the town has more than one reason to want August gone, and the emergence of deep betrayals and hidden promises that span generations threatens to reveal the truth behind Lily's death once and for all"--